- Thread starter
- #1

$$

A_{\lambda}=

\begin{pmatrix}

-\mu\lambda k^2 - k^2 - s & i\tau k & i\tau k - i\beta k^3\\

i\lambda k & \lambda + Dk^2 & -\alpha k^2\\

i\lambda k & 0 & \lambda

\end{pmatrix}

$$

where $\lambda = \lambda(k^2)$ (this is confusing) is the growth rate and k is the wave number, and tau, mu, D, alpha, s, and beta are biological parameters. The solvability condition for a matrix $A_{\lambda}$ requires that the matrix is singular.

So the I found the determinant to be $-Dk^4\lambda -Dik^2\lambda -Dk^2s\lambda +Di^2k^6\beta\lambda -k^2\lambda^2-ik^2\lambda^2-s\lambda^2+i^2k^4\beta\lambda^2-Dk^4\lambda^2\mu-k^2\lambda^3\mu-Di^2k^3\lambda\tau-i^2k^4\alpha\lambda\tau-i^2k\lambda^2\tau-i^2k^2\lambda^2\tau=0$

for it to be singular.

Then it says show that the polynomial associated with the solvability condition is given by

$$

a(k^2)\lambda^2 + b(k^2)\lambda +c(k^2) =0

$$

where

\begin{align}

a(k^2)=& \mu k^2\\

b(k^2)=& (\beta+\mu D)k^4 - (2\tau-1)k^2 s\\

c(k^2)=& \beta Dk^6-\{(\alpha+D)\tau-D\}k^4+sDk^2

\end{align}

From what I have, I can obtain that. I am not sure if i is the imaginary constant or just some constant i.

Even if i is the imaginary constant, we would still have some i's.

A_{\lambda}=

\begin{pmatrix}

-\mu\lambda k^2 - k^2 - s & i\tau k & i\tau k - i\beta k^3\\

i\lambda k & \lambda + Dk^2 & -\alpha k^2\\

i\lambda k & 0 & \lambda

\end{pmatrix}

$$

where $\lambda = \lambda(k^2)$ (this is confusing) is the growth rate and k is the wave number, and tau, mu, D, alpha, s, and beta are biological parameters. The solvability condition for a matrix $A_{\lambda}$ requires that the matrix is singular.

So the I found the determinant to be $-Dk^4\lambda -Dik^2\lambda -Dk^2s\lambda +Di^2k^6\beta\lambda -k^2\lambda^2-ik^2\lambda^2-s\lambda^2+i^2k^4\beta\lambda^2-Dk^4\lambda^2\mu-k^2\lambda^3\mu-Di^2k^3\lambda\tau-i^2k^4\alpha\lambda\tau-i^2k\lambda^2\tau-i^2k^2\lambda^2\tau=0$

for it to be singular.

Then it says show that the polynomial associated with the solvability condition is given by

$$

a(k^2)\lambda^2 + b(k^2)\lambda +c(k^2) =0

$$

where

\begin{align}

a(k^2)=& \mu k^2\\

b(k^2)=& (\beta+\mu D)k^4 - (2\tau-1)k^2 s\\

c(k^2)=& \beta Dk^6-\{(\alpha+D)\tau-D\}k^4+sDk^2

\end{align}

From what I have, I can obtain that. I am not sure if i is the imaginary constant or just some constant i.

Even if i is the imaginary constant, we would still have some i's.

Last edited: